Hepatitis C - von der individuellen Heilung zur weltweiten Elimination? - Böttler, Tobias; Lohmann, Volker; Bartenschlager, Ralf (Deutsche medizinische Wochenschrift, 2019)
With the implementation of highly effective direct acting antivirals (DAAs), global control or even elimination of chronic hepatitis C virus (HCV) infection might have come into reach. In fact, DAA therapy leads to complete virus elimination, defined as sustained viral response (SVR), in the vast majority of patients. Moreover, in patients without cirrhosis, the risk of developing HCC after DAA therapy is significantly reduced. For viremic patients who have already received DAA therapy, a distinction must be made between relapse and reinfection. The rate of new infections remains high and many infected individuals are undiagnosed. In order to come closer to the WHO goal of eliminating HCV worldwide by 2030, programs are needed to identify and treat all HCV-infected individuals. Strategies are missing in most countries to achieve this goal. Generic DAA therapies are available in some countries and appear to have similar cure rates compared to those obtained with the original drugs. The high variability of HCV, the numerous strategies of the virus to escape the immune response, and the lack of a suitable small animal model are key hurdles for vaccine development. Currently, the efficacy of two vaccine candidates is being investigated in clinical trials. The development of a protective vaccine is important, despite available therapy, to sustainably reduce the rate of new infections both in developing countries and in people with risk behavior.